Dental public health at a glance - Chestnutt, I. G. (Chichester, West Sussex, UK : Wiley Blackwell, 2016)
Dental Public Health at a Glance presents a richly-illustrated introduction to dental and oral health issues in communities and populations. Offering comprehensive coverage of this increasingly important field, each topic is presented in an easy-to-comprehend two-page spread with essential facts clearly summarized and accompanied by tables, illustrations and diagrams. Dental Public Health at a Glance covers a wide range of key concepts including: - Epidemiology - Evidence-based dentistry - Oral health promotion - The relationship of fluoride, diet, smoking, and alcohol to oral health - Assessment of health needs - Quality assurance in the provision of dental care - Considerations for a dental public health career Written by an expert in dental public health and offering illuminating insights into oral health at the population level, this is a must-have introductory textbook and revision guide for dentistry and dental hygiene and therapy students--Provided by publisher.
Epidemiology -- Evidence based dentistry -- Oral health promotion -- Fluoride and oral health -- Diet and oral health -- Smoking and oral health -- Alcohol and oral health -- Assessing health needs -- Providing dental services -- Quality assurance of dental care -- A career in dental public health.
Includes bibliographical references and index.
Keywords: Dental Health Services; Oral Health; Public Health Dentistry